2021
DOI: 10.1021/acs.joc.1c00453
|View full text |Cite
|
Sign up to set email alerts
|

CuI-Catalyzed Decarboxylative Thiolation of Propargylic Cyclic Carbonates/Carbamates to Access Allenyl Thioethers

Abstract: The first CuI-catalyzed decarboxylative thiolation of terminal alkyne-substituted cyclic carbonates/carbamates to access allenes has been developed. A wide range of hydroxymethyl-and aminomethylcontaining allenyl thioethers were smoothly obtained in good to excellent yields under mild conditions. The copper-allenylidene intermediate among the process is crucial to the decarboxylative thiolation reaction. This method opens up a new channel to access allenyl thioether compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…25). 48 Those obtained thioether-functionalized 2,3-allenols/2,3-allenamines could be easily converted into heterocycles such as various substituted pyrroles. Particularly, it was found that this method could directly deliver the pyrrole derivatives through a two-step one-pot process (Fig.…”
Section: Copper-catalyzed Decarboxylative Reactions Of 4-ethynyl-13-d...mentioning
confidence: 99%
“…25). 48 Those obtained thioether-functionalized 2,3-allenols/2,3-allenamines could be easily converted into heterocycles such as various substituted pyrroles. Particularly, it was found that this method could directly deliver the pyrrole derivatives through a two-step one-pot process (Fig.…”
Section: Copper-catalyzed Decarboxylative Reactions Of 4-ethynyl-13-d...mentioning
confidence: 99%
“…However, in stark contrast, the (2+n) cycloadditions of copper‐allenylidenes utilizing the α, β‐reactivity still belong to an unknown chemistry (Scheme 1c). The underdevelopment of this kind of (2+n) cycloadditions might be ascribed to the difficulties in controlling the regioselectivity in nucleophilic additions to copper‐allenylidenes because most of nucleophilic additions occurred on the γ‐position of copper‐allenylidenes [3–7] rather than the α‐position [8–10] . In fact, the challenges in realizing α,β‐regioselective (2+n) cycloadditions of copper‐allenylidenes mainly include: (1) controlling the α,β‐regioselectivity in nucleophilic additions to copper‐allenylidenes; (2) finding competent dinucleophiles with suitable reactivity to accomplish the (2+n) cycloadditions.…”
Section: Introductionmentioning
confidence: 99%
“…The underdevelopment of this kind of (2 + n) cycloadditions might be ascribed to the difficulties in controlling the regioselectivity in nucleophilic additions to copper-allenylidenes because most of nucleophilic additions occurred on the γ-position of copper-allenylidenes [3][4][5][6][7] rather than the α-position. [8][9][10] In fact, the challenges in realizing α,β-regioselective (2 + n) cycloadditions of copper-allenylidenes mainly include: (1) controlling the α,β-regioselectivity in nucleophilic additions to copper-allenylidenes; (2) finding competent dinucleophiles with suitable reactivity to accomplish the (2 + n) cycloadditions. Therefore, it is in a great demand to develop efficient strategies toward settling these challenges and realizing α,β-regioselective (2 + n) cycloadditions of copperallenylidenes.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] Only three nucleophiles, Grignard reagents, thioalcohol, and phosphine oxides were able to intermolecularly attack the a position to form the corresponding allenes. [23][24][25] Therefore, extra nucleophiles are typically necessary for such transformation. It remains undisclosed that nucleophiles generated in situ from the decarboxylation of cyclic carbonates are directly utilized for intramolecularly attacking the a position of Int I.…”
mentioning
confidence: 99%